Implementasi Karakter Religius dan Nasionalisme Melalui Bestari Camp di Sanggar Bimbingan Jalan Kebun, Malaysia - Kasmi, Kasmi; Rinenggo, Alil; Sutomo, Sutomo (Jurnal Kewarganegaraan, 2025)
The purpose of this study is to determine and implementation of religious and nationalistic characters through Bestari Camp at Sanggar Guidance Jalan Kebun, Malaysia. This research uses a descriptive qualitative method to describe and interpret the religious character and sense of nationalism. The research subjects include; Jalan Kebun Guidance Center Manager, Jalan Kebun Guidance Center Teacher, Bestari Camp Coordinator, Bestari Camp Participants. Data collection methods were carried out through several ways, namely observation, interviews, and literature studies. The application of religious and nationalism characters in Bestari Camp, which takes place at Jalan Kebun Guidance Studio, Malaysia, goes through important stages such as knowledge, feelings, and moral behavior. The results of the Jalan Kebun Guidance Center research show that the implementation of religious characteristics through religious activities, habituation of noble morals, and spiritual reflection. The implementation of the character of nationalism through Bestari Camp at Jalan Kebun Guidance Center through activities to deliver nationalism material, togetherness activities, respect for national symbols, tolerance and unity values, and appreciation of cultural diversity. The positive impact can be seen in the discipline, spiritual awareness, national spirit, as well as tolerance and mutual cooperation of the students of Jalan Kebun Guidance Center.